Effects of vitamin e supplementation on glycaemic control in type 2 diabetes: Systematic review of randomized controlled trials - N. Suksomboon (2018)
What is known and objective: Lowering haemoglobin A 1c (HbA 1c ) has clearly been shown to reduce microvascular complications of diabetes and possibly macrovascular disease and vitamin E has been suggested as a possibly useful intervention. Our aim is to evaluate the effect of vitamin E supplementation on glycaemic control in type 2 diabetes. Methods: Clinical studies of vitamin E were identified from computerized searches of MEDLINE, EMBASE, EBM reviews and the Cochrane Library up until November 2008. Historical searches of reference lists of relevant articles were also undertaken. To be included in our review, a study had to be: (i) a randomized controlled trial comparing vitamin E monopreparation against placebo or no treatment in patients with type 2 diabetes, (ii) lasting at least 8 weeks, and (iii) reporting glycated haemoglobin or HbA 1c . There was no language restriction. Study selection, data extraction and study quality assessment were performed by three reviewers with disagreement resolved by discussion. Treatment effect was estimated with the mean difference in the changes of HbA 1c from baseline to final assessment between the vitamin E and the control groups. Results: Nine trials involving 418 patients were included in this review. Vitamin E supplementation did not improve glycaemic control in the full set of type 2 diabetes patients. It was effective only in a subgroup of patients with inadequate glycaemic control at baseline (HbA 1c ≥8%) and in those whose baseline serum vitamin E levels were below normal ranges. The pooled mean difference in the changes of HbA 1c was -0·58% (95% CI -0·83% to -0·34%; P < 0·00001) which was the same for both subgroups of patients. What is new and conclusions: The evidence suggests no beneficial effect of vitamin E supplementation in improving glycaemic control in unselected patients with type 2 diabetes. However, HbA 1c may decrease with vitamin E supplementation in patients with inadequate glycaemic control or low serum levels of vitamin E. This shows the importance of targeting therapy. Due to the limitations of the available evidence, further studies are warranted. Also, the safety and long-term benefit of such supplements remain to be determined before its clinical benefit can be established unequivocably. © 2010 Blackwell Publishing Ltd.